Collection And Dissemination Of Satellite Remote Sensing Data: A Study On National Security Issue Of Sensed State - Lily Suryati, Mohd Jamil; Loh, Ing Hoe; Mohd Lotpi, Mohd Yusob; Salawati, Mat Basir (2015)
In the collection and dissemination of satellite remote sensing data, national security of sensed State has been the main issue to be considered. In order to uphold the sensed State’s rights as a sovereign State, Principles on Remote Sensing 1986 had been implemented. This article attempts to identify the discrepancy of principles between principle of common heritage of mankind and principle of sovereignty in its application to satellite remote sensing data. Besides, this article also attempts to identify the lacuna of law in the implementation of Principles on Remote Sensing 1986, in particular the issue of national security of the sensed State in the occasion of collection and dissemination of satellite remote sensing data. Finally, the writers will suggest some solutions to the problems that have been identified.